2019
DOI: 10.1159/000499501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic of Interatrial Block after an Acute ST-Segment Elevation Myocardial Infarction

Abstract: Background: The influence of interatrial block (IAB) in the prognosis after an acute ST-segment elevation myocardial infarction (STEMI) is unknown. Objectives: To assess the prognostic impact of IAB after an acute STEMI regarding long-term mortality, development of atrial fibrillation, and stroke. Methods: Registry of 972 consecutive patients with STEMI and sinus rhythm at discharge, with a long-term follow-up (49.6 ± 24.9 months). P wave duration was analyzed using digital calipers, and patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
5
0
1
Order By: Relevance
“…We read with great interest the study of Russo et al 1 regarding the prognostic role of interatrial block (IAB) among hospitalized COVID‐19 patients. Although the prognostic role of IAB has been previously described in several settings, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 this is the first report regarding the association of IAB with a poor prognosis in COVID‐19. The authors found that advanced IAB was an independent predictor of thrombotic events but did not include the data regarding patients with baseline atrial fibrillation.…”
mentioning
confidence: 76%
“…We read with great interest the study of Russo et al 1 regarding the prognostic role of interatrial block (IAB) among hospitalized COVID‐19 patients. Although the prognostic role of IAB has been previously described in several settings, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 this is the first report regarding the association of IAB with a poor prognosis in COVID‐19. The authors found that advanced IAB was an independent predictor of thrombotic events but did not include the data regarding patients with baseline atrial fibrillation.…”
mentioning
confidence: 76%
“…In recent years, aIAB has been reported for other populations as well, such as patients treated with transcatheter aortic valve implantation (12%) [33], patients with ST-elevation myocardial infarction (6%) [34] or takotsubo cardiomyopathy (5%) [35], patients with human immunodeficiency virus (4%) [36], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Partial IAB on admission and six hours post-PCI were independent predictors of atrial fibrillation at 12-month follow-up. In a registry study (n=972) of STEMI patients in sinus rhythm at hospital discharge, 21.3% had partial and 5.9% advanced IAB [9]. Patients with IAB had higher all-cause mortality than patients without IAB, but the association was explained by older age and other variables, while the multivariable analysis did not show any independent association between IAB and prognosis.…”
Section: Interatrial Blockmentioning
confidence: 91%